Pengaruh Perceived Social Support terhadap Psychological Well-Being Mahasiswa yang sedang Menyusun Skripsi - Azka Khoirunnisa; Dewi Rosiana (Universitas Kristen Maranatha, 2023)
For college student, thesis is a task that has challenges as well as obstacles in it which can become a stressor which ultimately can have an impact on disturbed mental health. When students have good psychological well-being, students are expected to be able to have adaptive coping in facing any difficulties and obstacles that arise in the process of writing their thesis. This research aims to determine the effect of perceived social support on psychological well-being in students who are writing their theses. The research uses a quantitative approach, with a causality design. The research subjects were obtained using a simple random sampling technique, consisting of 247 male and female students who were writing their theses at Bandung Islamic University, with ages ranging from 21 to 25 years. Data analysis uses simple linear regression analysis and descriptive statistical analysis. Data collection was carried out using measuring instruments that have been adapted to Indonesian, namely the Multidimensional Scale of Perceived Social Support (MSPPS) and using the Ryff Scale of Psychological Well-Being. The results of data analysis stated that there was a positive linear relationship and a significant influence of perceived social support on psychological well-being with a contribution value of 30.7% and with a significant value of 0.00 < alpha of 0.05. This means that the higher the social support that is felt to be useful and positive for students, the more it will increase the student's psychological well-being. It is best for educational institutions to provide support to students who are writing their theses by providing interventions based on perceived social support.